PROFESSOR ANATOLIY PETROVICH SAVCHENKO: ON THE OCCASION OF THE 75TH ANNIVERSARY OF HIS BIRTH (Вестник рентгенологии и радиологии, 2016)
Professor Anatoliy Petrovich SAVCHENKO: on the occasion of the 75th anniversary of his birth.